Patients' Preferences for Participation in Treatment Decision-Making at the End of Life: Qualitative Interviews with Advanced Cancer Patients - Brom, Linda (Public Library of Science, 2014)
PURPOSE: Patients are often encouraged to participate in treatment decision-making. Most studies on this subject focus on choosing between different curative treatment types. In the last phase of life treatment decisions differ as they often put more emphasis on weighing quantity against quality of life, such as whether or not to start treatment aimed at life prolongation but with the possibility of side effects. This study aimed to obtain insight into cancer patients' preferences and the reasons for patients' preferred role in treatment decision-making at the end of life. METHODS: 28 advanced cancer patients were included at the start of their first line treatment. In-depth interviews were held prior to upcoming treatment decisions whether or not to start a life prolonging treatment. The Control Preference Scale was used to start discussing the extent and type of influence patients wanted to have concerning upcoming treatment decision-making. Interviews were audio taped and transcribed. RESULTS: All patients wanted their physician to participate in the treatment decision-making process. The extent to which patients themselves preferred to participate seemed to depend on how patients saw their own role or assessed their own capabilities for participating in treatment decision-making. Patients foresaw a shift in the preferred level of participation to a more active role depending in the later phase of illness when life prolongation would become more limited and quality of life would become more important. CONCLUSION: Patients vary in how much involvement they would like to have in upcoming treatment decision-making. Individual patients' preferences may change in the course of the illness, with a shift to more active participation in the later phases. Communication about patients' expectations, wishes and preferences for participation in upcoming treatment decisions is of great importance. An approach in which these topics are openly discussed would be beneficial.